Aspects Of Justice Of Marriage Dispensation And Best Interests For Children - Imran, Imran; Suadi, Amran; Risnain, Muh.; Nurbani, Erlies Septiana (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Marriage dispensation is an application for a marriage permit made by the parents or family of a prospective husband or wife who is not yet 19 years old to enter into a marriage at the Religious Court. This paper briefly describes the justice of marriage dispensation and the children's best interests. The main topics discussed in this paper are the marriage laws and marriage dispensations according to the Law, the best interests of the child explained according to the Law, and to compromise between marriage dispensation and the child's best interests. The method used in this research is normative research by examining legal norms in legislation and decisions of the Constitutional Court. The content of this paper reveals that despite being deemed as contradictory to the Law as per the ruling of the Constitutional Court No. 22/PUU-XV/2017 dated 13 December 2018, which sets the minimum age for marriage according to Article 7 paragraph (1), child marriages facilitated by marriage dispensations persist in Indonesia. Furthermore, not every petition for marriage dispensation receives approval from the judicial panel. The decision on dispensation requests hinges on a thorough evaluation of the merits of the application and the potential impact on the child's future well-being, prioritizing the child's best interests.